The influence of project-based learning model on news-writing skills of students class VIII of MTSN 1 Jambi - Yasirotul Laelani (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to examine whether or not there is an effect of the projectbased learning model on the skills of writing news texts for class VIII MTsN 1 Jambi City in the 2022/2023 academic year. The population in this study were all students of class VIII MTs Negeri 1 Jambi City. After random sampling was carried out to determine the sample, Class VIII-D and VIII-G were selected as samples in this study, with 21 students in each class. Class VIII-D as the control class and VIII-G as the experimental class. This study uses quantitative research with a quasi-experimental research design (quasi-experiment). The instrument used by researchers to measure the success of the project-based learning model is a written test. The research data was obtained from the results of the pre-test and post-test given to the experimental class and control class. After obtaining the results of the students' pre-test and post-test, the researcher then analyzed the data using the SPSS version 25 program. From the results of data analysis it is known that in the post-test the experimental class obtained an average value of 82.81 which is in the good category. In contrast to the control class post-test which achieved an average value of 67.00 which is included in the less category. From this study also obtained the results of T count > T table 4.777 > 3.309 and sig. 0.000 <0.05, which means the hypothesis is accepted and proven true. The results of this study indicate that there is a change in the results of writing news texts for students after being given treatment using a project-based learning model in the experimental class. From that, the results of this study indicate that there is an influence of the project-based learning model on news text writing skills in class VIII MTs Negeri 1 Kota Jambi